Molecular biological effects of led-based photobiomodulation therapy on bone regeneration: a systematic review - Phan, Anh Chi; Tran, Le Huy; Nguyen, Nhat Thanh Chau; Dinh, Xuan Hai; Duong, Thi Thu Quyen; Hoang, Thi Nhu Quynh; Nguyen, Thi Phuong Thao; Phan, Duy An (Tạp chí Y Dược Huế, 2026)
Background: Bone regeneration is essential for dental procedures such as implant integration and orthodontic movement. Photobiomodulation (PBM), particularly using light-emitting diode (LED), has emerged as a promising non-invasive method to enhance bone healing, though its molecular mechanisms remain unclear and findings across studies are inconsistent. This systematic review aims to synthesize current evidence on the molecular effects of LED-based PBM on bone regeneration, focusing on bone formation and resorption. Materials and method: A systematic review was conducted following PRISMA 2020 guidelines. Literature searches were performed in PubMed and ScienceDirect up to November 10, 2024. Studies included full-text original research evaluating molecular effects of LED-PBM on bone compared to non-irradiated controls. Risk of bias was assessed using the QUIN tool for in vitro studies and SYRCLE for in vivo studies. Results: Out of 4646 articles, 16 met the eligibility criteria. Risk of bias was moderate to low overall, with some methodological limitations noted, particularly in blinding and allocation procedures. Wavelengths ranged from 405 to 830 nm, with red light being the most frequently used. Most studies reported increased expression of key osteogenic markers (ALP, RUNX2, OCN, OPN), improved calcium deposition, and modulation of inflammatory and signaling molecules ( ROS, ATP). Conclusion: This review confirms that LED-PBM promotes bone regeneration by upregulating key osteogenic markers and signaling pathways, offering a molecular basis for protocol refinement in dental applications.